PENGGUNAAN MODEL RASCH UNTUK MENDETEKSI KUALITAS SOAL KIMIA SMA PADA UJIAN AKHIR SEMESTER (UAS) - Pohan, Lisa Ariyanti; Ledya, Kiki; Setiawan, Vera Roni; Darmana, Ayi; Suyanti, Retno Dwi (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2022)
This study was conducted to analyze the questions for the Final Semester Examination (UAS) which were used to measure students' abilities in chemistry subjects in the science department of class XII of SMA Negeri 2 Lhokseumawe. Participants in this subject consist of 75 students. The questions given are in the form of multiple choice questions totaling 25 items related to integrated calculation and theory material in chemistry subject matter from class X, XI and XII. The Model Rasch is used to obtain fit items. This analysis was carried out with the help of Winsteps software. From the output of the Winsteps program, the results of the final semester exam (UAS) in chemistry subjects were tested using the Model Rasch to produce data, namely the item score (item reliability) of 0.77 with consistent information that the answers were in the sufficient category and the reliability of the person (person reliability) was 0.95. , with information on the quality of the items in the special category and Cronbach's alpha value of 0.85. The Outfit Mean Square Statistic (Outfitt MNSQ) value for the suitability of the questions and the level of difficulty of the questions is (1.54 = 1.5) in the person column. The Outfit Z Standard (Outfit ZSTD) value for the suitability of the questions and the level of difficulty of the questions in the item column is 0.55. The Outfit Mean Square Statistic (Outfitt MNSQ) value for students' abilities is 1.36 in the person column. The Outfit Z Standard (Outfit ZSTD) value for students' abilities in the item column is 0.19. The test questions used for chemistry subjects are 25 questions, after being tested with a fit Model Rasch, 18 questions (72%) can be used and as many as 7 questions (28%) are not fit or cannot be used.